Analisis dan Perancangan Sistem Informasi Pelayanan Meteorologi Penerbangan Pada Kantor Stasiun Meteorologi Klas 1 Sultan Thaha Jambi - Irawan, Arie; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2021)
The Sultan Thaha Jambi Class 1 Meteorological Station Office is a technical implementating unit under the Meteorology Climatology and Geophysical Agency which has the main duty and function of public services, namely providing aviation meteorological information services to support aviation safety. The information system in technological advances is a new challenge for the Sultan Thaha Jambi Class 1 Meteorological Station Office so that its services can be faster, more precise, accurate and recorded. One way to optimize the aviation meteorological services is using an information system. This research produces a prototype system. Where this research, researches use UML (Unified Modelling System) method as a design and development tool. This research produces a design from information system based on web which can be implemented furthermore so it can produce the information system of aviation meteorological services to the Sultan Thaha Jambi Class 1 Meteorological Statium Office.